Association of pregnancy outcomes with neonatal TSH levels in euthyroid singleton pregnancies - Feng, Weiwei; Song, Mengfan; Meng, Yu (Frontiers in Endocrinology, 2025)
BackgroundThe association between pregnancy outcomes and neonatal TSH levels remains controversial. The aim of this study is to explore the association between pregnancy outcomes and neonatal TSH to interpret neonatal TSH indicators reasonably.MethodsThis study was a large-sample, retrospective observational analysis conducted at a tertiary hospital in Shanghai. Data from 52,027 pregnant women who underwent routine prenatal examinations at the International Peace Maternity and Child Health Hospital from January 2013 to December 2016 were extracted from the electronic medical record system. The normal reference ranges for TSH and FT4 were established based on the 95% confidence interval of the total study population, and singleton pregnant women with normal thyroid function were selected for analysis. Non-parametric Mann-Whitney U test and Chi-square test were used to assess the relationship between pregnancy outcomes and neonatal TSH levels. A restricted cubic spline Cox regression model was used to evaluate the nonlinear association between various pregnancy outcomes and neonatal TSH. Univariate and multivariate logistic regression analyses were conducted to adjust for confounding factors and further analyze the relationship between pregnancy outcomes and elevated neonatal TSH levels.ResultsA total of 24079 pregnant women were included in this study. In univariate analysis, neonatal TSH levels were significantly higher in women with advanced maternal age and in multiparas (P < 0.05). Women with preeclampsia and cesarean section, neonates with fetal distress, male neonates, macrosomia, LBW and premature births had a significant increase in neonatal TSH level (P < 0.05). After adjusting for confounding factors, multivariate regression analysis showed that the following pregnancy outcomes remained strongly associated with neonatal TSH elevation (P<0.05): preeclampsia (OR=2.238, 95% CI 1.454 3.446), cesarean section (OR=1.404, 95% CI 1.179 1.672), advanced maternal age (OR=1.322, 95% CI 1.012 1.728), and preterm birth (OR=2.408, 95% CI 1.683 3.445).ConclusionNeonatal TSH levels are influenced by factors such as advanced maternal age, preeclampsia, cesarean delivery, and preterm birth, which can lead to elevated TSH in newborns.